Governo digital como mecanismo de transparência e efetivação do direito de acesso à informação pública. - Karen Bezerra Rosa Braga (Revista ft, 2026)
The digital transformation of the public sector has substantially changed the way governments organize administrative activities, deliver public services and provide information to society. Within this context, digital government has emerged as a management model based on the strategic use of information and communication technologies to improve administrative efficiency, enhance transparency and foster citizen participation. This study examines the relationship between digital government and public information transparency, analyzing the progress achieved in Brazilian public administration, the legal framework supporting this transformation and the principal challenges affecting its implementation. The research adopts a qualitative, exploratory and descriptive approach through bibliographic and documentary review, considering scientific literature, legislation and publications issued by international organizations specialized in public governance. The findings indicate that digital government constitutes an important mechanism for strengthening administrative transparency, social oversight and institutional efficiency.